CROSS-WORLD NARRATIVES AND TRAVELS: RECONSTRUCTING THE HISTORY OF EARLY SYRIAN-AMERICAN IMMIGRANTS - Haidar, Otared (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2024)
Narratives of travel are part of world literature and cultural history. Scholarly research on migrant narratives and literature is a subfield of intercultural studies and comparative literature which allow cultures to bond and interact. Written histories of Arab Americans start with the Foundational Period (1880-1920) which revolves around the early immigrants from Historical Syria. This period is one of the least documented eras which is still difficult to reconstruct due to its many gaps and various obstacles. This paper examines the strategies and approaches used by Philip Hitti, the founder of Arabic Studies in the United States, who established the master models and approaches for the study of the Syro-Lebanese immigrant community. This model is based on locating alternative sources that include ̶ in addition to official sources and written accounts ̶ folksongs, literary texts, popular stories, and personal memories. It makes use of them to reconstruct the history of this community, which is characterized by its rich popular culture and long tradition of story-telling. There may be polemics and prejudices in presenting the wealth of the oral and cultural tradition of Historical Syria’s communities in the mainstream popular and official narratives about Arabs and Muslims. When presented with scholarly research and comparative perspectives, immigrants’ narratives can have a valuable contribution to world literature on immigration.